2019
DOI: 10.1080/17539153.2019.1629860
|View full text |Cite
|
Sign up to set email alerts
|

Securitising education: an exploration of teachers’ attitudes and experiences regarding the implementation of the Prevent duty in sixth form colleges

Abstract: The government's counter-terrorism policy, known as CONTEST, has four components, Pursue, Protect, Prepare and Prevent. The counter terrorism and security act in 2015 led to changes to Prevent by placing a legal duty on frontline staff, such as teachers, to enact Prevent in schools and colleges. Currently, the impact of these changes is not well understood, and the present study explores the attitudes and experiences of college teachers regarding the implementation of the Prevent duty. Fourteen participants, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
1
19
0
4
Order By: Relevance
“…Several studies explicitly address the difficulties teachers face in recognising radicalisation. Moffat and Gerard (2019, p. 3) emphasise that radicalisation is not well understood and suggest that this makes it ‘a near impossible task for teachers’ to identify risk of radicalisation. Indeed, their interviews with London‐based college teachers identify concerns about ‘judging the signs of radicalisation’, which was deemed ‘difficult to assess’ (Moffat and Gerard, 2019, p. 11).…”
Section: Extant Knowledge: Evaluating the Ability To Recognise And Respond To Radicalisationmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies explicitly address the difficulties teachers face in recognising radicalisation. Moffat and Gerard (2019, p. 3) emphasise that radicalisation is not well understood and suggest that this makes it ‘a near impossible task for teachers’ to identify risk of radicalisation. Indeed, their interviews with London‐based college teachers identify concerns about ‘judging the signs of radicalisation’, which was deemed ‘difficult to assess’ (Moffat and Gerard, 2019, p. 11).…”
Section: Extant Knowledge: Evaluating the Ability To Recognise And Respond To Radicalisationmentioning
confidence: 99%
“…Moffat and Gerard (2019, p. 3) emphasise that radicalisation is not well understood and suggest that this makes it ‘a near impossible task for teachers’ to identify risk of radicalisation. Indeed, their interviews with London‐based college teachers identify concerns about ‘judging the signs of radicalisation’, which was deemed ‘difficult to assess’ (Moffat and Gerard, 2019, p. 11). Similarly, Bryan (2017) found that teachers struggled to articulate a process of radicalisation.…”
Section: Extant Knowledge: Evaluating the Ability To Recognise And Respond To Radicalisationmentioning
confidence: 99%
See 2 more Smart Citations
“…2 For examples of research exploring the duty within education that utilise interviews as method see, Authors, 2018;Revell, 2019;Moffat and Gerard, 2020. For similarly inclined studies focused on health see, Heath-Kelly and Strausz (2019) and Younis and Jadhav's two ethnographic studies (2019a;. Upon receiving replies we began inputting our data by institution into a spreadsheet and then started the process of surveying the entire dataset for initial codes, themes and features.…”
Section: Using Freedom Of Information Requestsmentioning
confidence: 99%